Comparison of Methods for the Estimation of Total Inorganic Nitrogen Deposition to Forests in Germany - Ahrends, Bernd; Schmitz, Andreas; Prescher, Anne-Katrin; Wehberg, Jan; Geupel, Markus; Andreae, Henning; Meesenburg, Henning (Frontiers in Forests and Global Change, 2020)
A reliable quantification of total inorganic nitrogen (TIN) deposition to forests is required for the evaluation of ecological effects of TIN inputs to forests and to monitor the success of clean-air policy. As direct measurements are scarce, different modelling approaches have been developed to estimate TIN deposition to forests. Three common methods are the (i) “canopy budget model”, (ii) “inferential method” and (iii) “emission based estimates” using a chemical transport model. Previous studies have reported considerable and site-specific differences between these methods, complicating the interpretation of results. We use data from more than 100 German intensive forest monitoring sites over a period of 16 years for a cross-comparison of these approaches. Nonlinear mixed-effect models were applied to evaluate how factors like meteorology, terrain and stand characteristics affect discrepancies between the model approaches. Taking into account the uncertainties in deposition estimates, there is a good agreement between the canopy budget and the inferential method when using semi-empirical correction factors for deposition velocity. Wet deposition estimates of the emission based approach were in good agreement with wet-only corrected bulk open field deposition measurements used by the other two approaches. High precipitation amounts partly explained remaining differences in wet deposition. Larger discrepancies were observed when dry deposition estimates are compared between the emissions based approach and the other two approaches, which appear to be related to a combination of meteorological conditions and tree species effects.